Pengembangan Media Interaktif Powerpoint untuk Meningkatkan Literasi Budaya dan Kewargaan Di Sekolah Dasar - Lina Indi Ainulmila; Wuli Oktiningrum (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to develop interactive PowerPoint media to increase cultural literacy and citizenship in schools. This research is an RD research referring to the Borg Gall model covering 7 of 10 stages, namely information gathering, planning, preliminary product development, initial field trials, initial product revisions, main field trials, and main product revisions. Data collection techniques using observation, interviews, questionnaires, product assessment, and tests. The study results showed that PowerPoint interactive learning media is valid to use and can increase cultural literacy and citizenship in thematic learning in elementary schools.